Pengaruh Media Pembelajaran Interaktif Berbasis Digital Terhadap Kemampuan Literasi Dan Numerasi Siswa Madrasah Ibtidaiyah Azzainiyah II - Feriska Listrianti; Meylan Paputungan; Rifqotul Amanatil Qowiyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The use of interactive digital-based learning media has become an increasingly important topic in the field of education, especially at MI Azzainiyah II. This media offers the potential to enhance students' literacy and numeracy skills and enrich their learning experiences. However, to maximize its benefits, it is important to understand the perceptions and experiences of students, teachers, and educational staff regarding the use of this media. This research utilizes an interview approach as the primary method for data collection. Interviews are conducted with two groups of participants: students of Madrasah Ibtidaiyah Azzainiyah II and teachers/educational staff involved in the use of interactive learning media. The interview questions focus on the students' level of literacy and numeracy, their learning experiences, the effectiveness of learning media, and the challenges faced by teachers in integrating this media into the curriculum. From the results of the interviews with students, it is expected to reveal how interactive learning media contributes to improving their literacy and numeracy skills. Furthermore, students' perceptions and experiences in using this media will also be analyzed. From the interviews with teachers and educational staff, the effectiveness of using this learning media in enhancing classroom learning will be discussed. The challenges faced by teachers in integrating this media and the solutions they propose will also be an important part of the discussion. The results of this research are expected to provide valuable insights for further development in the use of interactive learning media at MI Azzainiyah II.